2021
DOI: 10.48550/arxiv.2102.10150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Magnetized discs and photon rings around Yukawa-like black holes

Alejandro Cruz-Osorio,
Sergio Gimeno-Soler,
José A. Font
et al.

Abstract: TABLE I. Summary of space-time and disc properties-in geometrized units -for our three values of the length scale λ and some representative values of δ. From left to right the columns report the radii of the event horizon r EH , of the marginally bound orbit r mb , of the cusp of the gravitational potential rcusp, of the inner edge of the disc rin, of the center of the disc rc, and of the outer edge of the disc rout, as well as the specific angular momentum l mb at r mb , the gap of the potential ∆W, the angul… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In a number of interesting works, it is shown that the BH shadow can be investigated in interplay with other relevant ideas such as QNMs, deflection light and quasiperiodic oscillations (QPO) [102]- [112]. Additionally, it is known that the GTR-based magnetohydrodynamic simulations of the magnetized accretion flow onto BH can reveal more details of the BH shadow, see e.g [113][114][115][116].…”
Section: Introductionmentioning
confidence: 99%
“…In a number of interesting works, it is shown that the BH shadow can be investigated in interplay with other relevant ideas such as QNMs, deflection light and quasiperiodic oscillations (QPO) [102]- [112]. Additionally, it is known that the GTR-based magnetohydrodynamic simulations of the magnetized accretion flow onto BH can reveal more details of the BH shadow, see e.g [113][114][115][116].…”
Section: Introductionmentioning
confidence: 99%
“…In a number of interesting works, it is shown that the BH shadow can be investigated in interaction with other relevant ideas such as QNMs, deflection light and quasiperiodic oscillations (QPO) [102]- [112]. Additionally, it is believed that in the light of the GTR-based magnetohydrodynamic simulations of the magnetized accretion flows onto BH, thereby, more details of the BH shadow will become reveals for us, see e.g [113][114][115][116].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, proofs of concept of the feasibility of testing general relativity, or even the existence of new particles via EHT observations have been reported in, e.g. [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%